An Approach to Avoid Hypoglycemia: A Model for Mealtime Insulin Dose Calculation for Diabetic People - Deepali Javale; Sharmishta Desai (U.Porto Journal of Engineering, 2025)
Background: It has been observed that the number of diabetes patients has steadily increased over the past decades. Particularly, Type 1 diabetics are required to use insulin therapy to maintain their blood glucose levels. Technological advancements in the production of insulin pumps and monitoring devices have aided diabetics in maintaining a healthy lifestyle. A patient with type 1 Diabetes Mellitus (DM) requires insulin therapy with profound roots. Most diabetics require a minimum of two daily insulin injections, with dosage adjustments dependent on self-monitoring of blood glucose levels.